The Thermal Effect on PLA And PLA / Curcumin Composite Properties under Positron Annihilation Lifetime Spectroscopy - Nuri, Saygin M.; Hasan, Shanay Rajab; Mohammed, Hussein Ali (Iraqi Journal of Science, 2021)
In this study, pure polylactic acid (PLA) and composite polylactic acid/ curcumin (PLA / Cur) were prepared by a suspension of ultrasonically agitated micrometer-sized curcumin powder, which was mixed with chloroform solvent under slow mechanical stirring and incorporated into the PLA. The resulting suspension was used to cast free-standing PLA / Cur composite films. The filler content was chosen to be 2.0 wt % curcumin. Physical properties (glass transition, temperature, mechanical and thermodynamic) were analyzed by Positron Annihilation Lifetime Spectroscopy (PALS), which is a unique tool for analyzing the defects of polymer materials. The free volume and holebility of PLA and PLA / Cur were studied in vacuum and temperature range of 283 to 353 K. Ortho-positronium (o Ps), life , and intensity were measured as more sensitive parameters to determine free volume dimensions. The results of the thermodynamic property of PLA, examined with PALS technique, revealed a phase change of around 58 ºC. Also, an improvement was observed in the PLA / Cur structure with the addition of curcumin, by reducing nano-size defects.